The facilitators and barriers of physical activity among Aboriginal and Torres Strait Islander regional sport participants - Peloquin, C.; Doering, T.; Alley, S.; Rebar, Amanda (Wiley-Blackwell Publishing Asia, 2017)
Â© 2017 The Authors Background: Disparities in health perspectives between Indigenous and non-Indigenous populations are major concerns in many of the world's well-developed nations. Indigenous populations are largely less healthy, more prone to chronic diseases, and have an earlier overall mortality than non-Indigenous populations. Low levels of physical activity (PA) contribute to the high levels of disease in Indigenous Australians. Method: Qualitative analysis of structured one-on-one interviews discussing PA in a regional setting. Participants were 12 Indigenous Australian adults, and 12 non-Indigenous Australian adults matched on age, sex, and basketball division. Results: Most participants reported engaging in regular exercise; however, the Indigenous group reported more barriers to PA. These factors included cost, time management and environmental constraints. The physical facilitators identified by our Indigenous sample included social support, intrinsic motivation and role modelling. Conclusion: Findings describe individual and external factors that promote or constraint PA as reported by Indigenous Australian adults. Results indicate that Indigenous people face specific barriers to PA when compared to a non-Indigenous sample. Implications for public health: This study is the first to compare the perspective of Indigenous Australians to a matched group of non-Indigenous Australians and provides useful knowledge to develop public health programs based on culturally sensitive data.